Unlocking efficiency in column chromatography with packed bed supporting inserts - Romone M. Fancy; David H. Abraham; Matthew R. Taylor; Cole McMullin; Nicholas S. Brann; Daniel M. Bailey; David I. Brown; Heather Bethea Horne; Leslie S. Wolfe (Frontiers in Bioengineering and Biotechnology)
To purify increasing amounts of biotherapeutics more efficiently, the use of high flow rates or greater resin bed heights during downstream chromatography steps is a tantalizing option. A limitation of utilizing high flow rates is the differential pressure generated by packed chromatography resin beds. As a resin bed height increases, the resin is susceptible to compression. By increasing the permeability of a packed resin bed through control of the hydraulic radius, column pressure-flow dynamics can be improved. Chromatography column performance using a commercially available Protein A resin was assessed with and without OMEGA, a column insert designed to modulate the hydraulic radius of the column by providing vertical supports through the packed resin bed. OMEGA was shown to reduce the effective hydraulic radius of packed resin beds, increase the permeability of packed columns by 44%–73%, and yield a 42%–50% decrease in pressure differential across the resin bed at a comparable linear velocity. The structural support provided by OMEGA enables higher operational flow rates and increased resin bed height without impact to either dynamic binding capacity or purified product quality. With the OMEGA column insert, scale-up hurdles are mitigated, and faster downstream processing times are unlocked across column geometries.